1991
DOI: 10.1007/978-94-011-3792-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of gestating female Sebastes schlegeli: estimating the reproductive costs of livebearing

Abstract: SynopsisDuring gestation, live-bearing fishes incur physiological energy costs, including provision of energy and respiratory gases to the developing embryos and removal of waste products. Fecundity in the genus Sebastes is high, and the ovaries represent a significant portion of the weight of gestating females. In this study, we compare oxygen consumption of gestating females with non-gestating females and males of kurosoi, Sebastes schlegeli, to estimate these costs. Oxygen consumption by pregnant females is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…3). However, these differences are possibly due to differences in methodology (Boehlert et al 1991) and the less frequent developmental intervals tested (Dygert & Gunderson 1991).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3). However, these differences are possibly due to differences in methodology (Boehlert et al 1991) and the less frequent developmental intervals tested (Dygert & Gunderson 1991).…”
Section: Discussionmentioning
confidence: 96%
“…It also showed that subtle environmental changes such as changes in light conditions can affect metabolism measurements. The methods used by Boehlert et al (1991) on S. schlegeli differed considerably with acclimations of 3-5 minutes and average measurement periods of 43 minutes. While this may have been appropriate for the cultured and domesticated S. schlegeli it would have been unsuitable for the wild S. flavidus used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have reported elevated metabolic rate (Webb and Brett, 1972;Boehlert et al, 1991;Hopkins et al, 1995;Timmerman and Chapman, 2003;Skov et al, 2010) and diminished swimming performance (Plaut, 2002;Ghalambor et al, 2004;Belk and Tuckfield, 2010) in pregnant live-bearing fish. The studies differ from the present study in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated metabolic rate in relation to gravidity or pregnancy has been reported in many animals, including the eastern garter snake (Thamnophis sirtalis) (Birchard et al, 1984), mountain spiny lizard (Sceloporus jarrovi) (DeMarco, 1993), yellowtail rockfish (Sebastes flavidus) (Hopkins et al, 1995), Korean rockfish (Sebastes schlegeli) (Boehlert et al, 1991), sailfin molly (Poecilia latipinna) (Timmerman and Chapman, 2003), striped surfperch (Embiotoca lateralis) (Webb and Brett, 1972) and European eelpout (Zoarces viviparus) (Skov et al, 2010). Several studies have demonstrated diminished locomotor performance caused by gravidity or pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Rockfishes all have internal fertilisation, an unusual feature among marine teleosts, and matrotrophic viviparity has been shown in some species (e.g. Boehlert et al, 1991). The very large number of species is undoubtedly their best known attribute, as Sebastes represents the most numerous genus in the family Scorpaenidae, with more than 110 species worldwide (Eitner et al, 1999;Nelson, 1994).…”
Section: Introductionmentioning
confidence: 99%